2017
DOI: 10.1080/15284336.2017.1330801
|View full text |Cite
|
Sign up to set email alerts
|

HIV-coinfected patients respond worse to direct-acting antiviral-based therapy against chronic hepatitis C in real life than HCV-monoinfected individuals: a prospective cohort study

Abstract: HIV-coinfection is associated with worse response to DAA-based therapy against HCV infection. In patients receiving IFN-free therapy, this fact seems to be mainly driven by a higher rate of relapses among HIV-coinfected subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
1
24
0
3
Order By: Relevance
“…These results contrast with the recently published findings of Neukam et al, which suggested that HIV-coinfected patients respond less well to DAA-based therapy. The authors discuss a higher frequency of liver cirrhosis in the HIV-coinfected patients as a possible explanation for their findings [15]. Liver cirrhosis has indeed been described as a risk factor for lower response rates in some studies, especially in GT 3 patients [16,17].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…These results contrast with the recently published findings of Neukam et al, which suggested that HIV-coinfected patients respond less well to DAA-based therapy. The authors discuss a higher frequency of liver cirrhosis in the HIV-coinfected patients as a possible explanation for their findings [15]. Liver cirrhosis has indeed been described as a risk factor for lower response rates in some studies, especially in GT 3 patients [16,17].…”
Section: Discussionmentioning
confidence: 87%
“…Showing higher relapse rates and lower cure rates in HIV/HCV‐coinfected individuals, they also conclude that shortening of treatment duration in these patients should be discussed critically. Their data support the findings from the ALLY‐2 clinical trial, which showed higher relapse rates after 8 weeks of daclatasvir + sofosbuvir therapy in HIV/HCV‐coinfected subjects than the 12 week treatment arm . It is important to highlight, though, that all relapses in the ALLY‐2 trial only occurred in patients with higher baseline HCV viral loads.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While response to DAA treatment in HIV/HCV coinfected patients tended to be lower in the early DAA era, modern HCV DAA regimens yield SVR rates in HIV/HCV coinfected patients of >95%, and thus, HIV/HCV coinfected patients no longer represent a ‘difficult‐to‐cure’ patient population . We observed a response rate of 64.7% (22/34) to PEGIFN‐based treatment vs 87.5% (49/56) to DAA‐based regimens in our study cohort.…”
Section: Discussionmentioning
confidence: 63%
“…[3][4][5][6][7][8][9][10] For HIV/HCV-coinfected patients, high rates of SVR have also been reported. [7][8][9][10][11][12][13] However, it is not known whether some benefits of SVR to PegIFN/RBV on nonhepatic outcomes might be extrapolated to DAA. On the contrary, some clinical events, such as HCC, herpes virus and hepatitis B virus reactivations, have been suggested to be related with the use of DAA combinations.…”
Section: Introductionmentioning
confidence: 99%